Gels Synthesis, Characterization and Applications in High Performance Chemistry - Paun, Viorel-Puiu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Organogels, hydrogels, and ionic gels have been investigated both in a theoretical and experimental manner. The research performed was focused on their synthesis and applications in high-performance chemistry and its important branches. All mentioned gels were characterized from structural and supramolecular points of view by FTIR, NMR, X-ray diffraction, and POM. The keywords proposed in this reprint were as follows: organogels, hydrogels, ionic gels, chitosan, and fractal analysis. These terms were extremely pertinent to this research piece, hereby presented. As a result, all reference themes, as well as those associated with them, were touched upon in this reprint. We mention that the articles in this selection focused on one or more of the topics listed above.